2021
DOI: 10.1111/jce.15019
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant treatment of atrial fibrillation during mitral valve surgery

Abstract: Introduction Surgical management of atrial fibrillation (AF) is a well‐established method of preventing complications and late mortality in patients presenting with AF before mitral valve (MV) surgery. However, despite a substantial body of evidence and a Class I recommendation to apply surgical ablation (SA) concomitant to MV surgery, the utilization of SA remains low. Methods In this study, we sought to summarize the current trends in the SA of AF during MV surgery and update the medical community on its adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…According to these, the long-term outcome in surgically treated patients with concomitant paroxysmal AF is significantly less favorable and worsens with increasing AF burden. Furthermore, the evidence for positive effects on mortality by simultaneous surgical ablation of AF during mitral valve surgery mentioned in the introduction opposes the present results [9]. If our results are interpreted in comparison with AF patients without concomitant relevant MR, they may also seem unexpected or even controversial in light of recent findings on the positive prognostic effects of rhythm control therapy, as for example reported in the "Catheter Ablation versus Standard Conventional Therapy in Patients with Left Ventricular Dysfunction and Atrial Fibrillation" (CASTLE-AF) trial and in recent pooled analyses of randomized data or metaanalyses [17][18][19].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…According to these, the long-term outcome in surgically treated patients with concomitant paroxysmal AF is significantly less favorable and worsens with increasing AF burden. Furthermore, the evidence for positive effects on mortality by simultaneous surgical ablation of AF during mitral valve surgery mentioned in the introduction opposes the present results [9]. If our results are interpreted in comparison with AF patients without concomitant relevant MR, they may also seem unexpected or even controversial in light of recent findings on the positive prognostic effects of rhythm control therapy, as for example reported in the "Catheter Ablation versus Standard Conventional Therapy in Patients with Left Ventricular Dysfunction and Atrial Fibrillation" (CASTLE-AF) trial and in recent pooled analyses of randomized data or metaanalyses [17][18][19].…”
Section: Discussioncontrasting
confidence: 90%
“…This highlights why AF cannot be considered as a negligible benign concomitant disease and why additional strategies are urgently needed to improve the prognosis of this special and still growing cohort of patients. While there is strong evidence for prognostically favorable concomitant rhythm control of AF in the collective of surgically treated MR patients, reflected in a class I recommendation in the relevant guidelines, data on the effects of therapy for AF in the TMVR cohort are lacking [9][10][11]. Therefore, the aim of the present study is to elucidate the impact of different strategies for the treatment of concomitant AF on the outcome of TMVR patients.…”
Section: Introductionmentioning
confidence: 98%
“…10 At Northwestern University in Chicago, our overall use of PPM's after SA for a variety of operations is 7.9%, but it varies considerably by operation, and is less than 1% for patients undergoing surgical ablation with isolated mitral repair. 11 Some reports note that the PPM implantation rate is higher for patients who receive a "biatrial" lesion set compared to left atrial only ablation or pulmonary vein isolation. Both the Maze-III and Maze-IV procedures include right atrial lesions.…”
Section: High Variability In the Use Of New Permanent Pacemaker Impla...mentioning
confidence: 99%
“…However, In the CTS Net randomized trial the need for PPM was associated with a higher risk of 1‐year mortality (hazard ratio [HR] 3.21) 10 . At Northwestern University in Chicago, our overall use of PPM's after SA for a variety of operations is 7.9%, but it varies considerably by operation, and is less than 1% for patients undergoing surgical ablation with isolated mitral repair 11 …”
Section: Introductionmentioning
confidence: 99%
“…Only 38% of patients with preoperative AF who underwent mitral valve surgery have concomitant ablation. The slow adoption of the guidelines is in part due to the perceived complexity of the surgical AF ablation procedure ( 3 ) and possible increased risks for postoperative permanent pacemakers (PPM) ( 4 ). Furthermore, previous studies have shown that the left atrium diameter (LAD) was an important prognostic factor for patients received mitral valve surgery and AFRA with conflicting findings.…”
Section: Introductionmentioning
confidence: 99%